Amphiregulin antibody and reduction of axial elongation in experimental myopia - Jiang, Wen Jun; Jonas, Jost B. (EBioMedicine, 2017)
To examine the mechanism of ocular axial elongation in myopia, guinea pigs (age: 2-3weeks) which either underwent unilateral or bilateral lens-induced myopization (group 1) or which were primarily myopic at baseline (group 2) received unilateral intraocular injections of amphiregulin antibody (doses: 5, 10, or 15μg) three times in intervals of 9days. A third group of emmetropic guinea pigs got intraocular unilateral injections of amphiregulin (doses: 0.25, 0.50 or 1.00ng, respectively). In each group, the contralateral eyes received intraocular injections of Ringer's solution. In intra-animal inter-eye comparison and intra-eye follow-up comparison in groups 1 and 2, the study eyes as compared to the contralateral eyes showed a dose-dependent reduction in axial elongation. In group 3, study eyes and control eyes did not differ significantly in axial elongation. Immunohistochemistry revealed amphiregulin labelling at the retinal pigment epithelium in eyes with lens-induced myopization and Ringer's solution injection, but not in eyes with amphiregulin antibody injection. Intraocular injections of amphiregulin-antibody led to a reduction of lens-induced axial myopic elongation and of the physiological eye enlargement in young guinea pigs. In contrast, intraocularly injected amphiregulin in a dose of ≤1ng did not show a significant effect. Amphiregulin may be one of several essential molecular factors for axial elongation.